The Hepatotoxic and Nephrotoxic Effects of Purwoceng (Pimpinella pruatjan Molk.) Roots Ethanol Extract Administration in Subchronic Dose - Fitranto Arjadi; Nur Signa Aini Gumilas; Ika Murti Harini; Vitasari Indriani; Lantip Rujito (Molekul, 2021)
Purwoceng (Pimpinella pruatjan Molk) is an original Indonesian herb which is known to have an aphrodisiac effect. The active compounds in Purwoceng potentially have hepatotoxic and nephrotoxic effects.This study was aimed to analyze the effect of subchronic administration of Purwoceng roots ethanol extract to Wistar Strain of Rattus norvegicus rats. The method of this subchronic toxicity study was an experimental post test only with control group design. Forty male Rattus norvegicus were randomly divided into four groups and get 28-days treatment. Group A as control received aquadest and 1% CMC (carboxymethyl cellulose), group B, C, and D were given Purwoceng roots ethanol extract of 42, 84, and 168 mg/KgBW/day and 1% CMC. Parameters tested were the levels of urea, creatinine, SGPT (serum glutamic pyruvic transaminase), SGOT(serum oxaloacetic pyruvic transaminase), kidney and hepar histopatology.The results showed a statistically significant for the liver histopathological in group B, creatinine, urea, and kidney histopathology  in group C. Our study concluded that subchronic administration of Purwoceng (Pimpinella pruatjan Molk) roots ethanol extract could induce hepatotoxicity at the 42 mg/KgBW/day dose level and nephrotoxicity at the 84 mg/KgBW/day dose level.